Efficacy and Safety of Resilient Hyaluronic Acid Fillers Injected with a Cannula: A Randomized, Evaluator-Blinded, Split-Face Controlled Study [Corrigendum] - Beer, Kenneth; Biesman, Brian; Cox, Sue Ellen; Smith, Stacy; Picault, Laura; Trevidic, Patrick (Clinical, cosmetic and investigational dermatology, 2023)
Beer K, Biesman B, Cox SE, Smith S, Picault L, Trevidic P. Clin Cosmet Investig Dermatol. 2023;16:959-972. The authors advised an inadvertent error at the time of figure assembly led to the selection of incorrect versions of graphs displayed in Figure 1 on page 964 (ie, needle and cannula legends were switched) and Figure 4B on page 965 (ie, incorrect label values for timepoint V3). Consequently, result description and discussion associated with Figure 1 in this publication were opposite to what is actually observed. Page 963, Injection Volume and Technique section, second paragraph, last sentence, the text "However, there were slightly more "very easy" versus "easy" answers for the cannula-treated side (Figure 1)" should read "However, there were slightly more "very easy" versus "easy" answers for the needle-treated side (Figure 1)". Page 969, second paragraph from the bottom, last sentence, the text "For some practitioners, cannula injections may be seen as an "advanced" technique, yet the higher "ease of injection" scores obtained in the present study show that this technique is easier to use than a needle injection" should be deleted. The interpretation of results shown in Figure 4B remain accurate. The authors apologize for these errors. The correct Figures 1 and 4 are shown below. Figure 1 Ease of injection of RHA 4 into the nasolabial fold with a cannula or a needle, according to the treating investigator. Figure 4 Percentage of subjects rated "improved" or "much improved" on the Global Aesthetic Improvement Scale at each visit by the treating investigator (A) and the subjects (B).